Disaster Management Among Dental Graduates in a Private Dental Institution in India: A Pilot Study. (4th March 2014) - Chhabra, Kumar Gaurav; Rajesh, Guru Raghavendran; Shetty, Preetha J.; Prasad, Kakarla V V; Chhabra, Chaya; Muddapur, Mahadevayya
Abstract Objective To obtain insights into disaster management among dental graduates in a dental institute in India. Methods A total of 103 of 104 house surgeons in Shri Dharmasthala Manjunatheswar College of Dental Sciences and Hospital, Dharwad, participated in the main study (response rate = 99.04%). Their knowledge, attitude, and behavior regarding disaster management were assessed by use of a survey questionnaire. Information was also collected regarding age, gender, religion, and residence. Results Mean knowledge, attitude, and behavior scores toward disaster management were 45.46%, 79.53%, and 37.70%, respectively. A significant relationship was observed between knowledge and attitude scores (r = 0.248, P = .012). No significant differences were found in knowledge, attitude, and behavior by gender, religion, and residence. Religion was a significant predictor of knowledge scores (χ2 = 10.108, P = .006). Conclusions Respondents had favorable attitudes toward disaster management, but their knowledge and behavior required considerable improvement. Knowledge of the respondents was significantly associated with their attitude. This pilot study highlights the need for curriculum changes in dental education in India and further nationwide study. (Disaster Med Public Health Preparedness. 2014;0:1-7)